The Performance of Emotional Labour in Psychologists Conducting Psychotherapy - Clarke, James J. (Curtin University, 2023)
Factors contributing to burnout in psychologists providing psychotherapy has been explored previously but the potential contribution of emotional labour has been neglected. I present findings from mixed-methods research drawn from semi-structured interviews and an online survey. A link between emotional labour, burnout, and other outcomes is established. Findings also significantly contribute to literature regarding contributing factors to emotional labour in psychologists, conceptualisation and measurement of emotional labour, and potential strategies to manage emotional labour effectively.